2021
DOI: 10.1186/s12902-021-00714-9
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein A1 is negatively associated with male papillary thyroid cancer patients: a cross-sectional study of single academic center in China

Abstract: Background Papillary thyroid cancer (PTC) is the most common type of thyroid cancer and the incidence of PTC has continued to increase over the past decades. Many studies have shown that obesity is an independent risk factor for PTC and obese PTC patients tend to have a relative larger tumor size and higher grade of tumor stage. Obesity is associated with disordered lipid metabolism and the relationship between serum lipids and PTC remains unclear. Therefore, this study aimed to investigate the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 24 publications
0
7
1
Order By: Relevance
“…( 32 ). Some retrospective observational studies have reported an association between total cholesterol ( 31 ) and apolipoprotein A1 ( 33 ) with thyroid cancer, which is somewhat inconsistent with the results of our study. In the observational study, HDL may be a confounding factor for other lipid profiles.…”
Section: Discussioncontrasting
confidence: 99%
“…( 32 ). Some retrospective observational studies have reported an association between total cholesterol ( 31 ) and apolipoprotein A1 ( 33 ) with thyroid cancer, which is somewhat inconsistent with the results of our study. In the observational study, HDL may be a confounding factor for other lipid profiles.…”
Section: Discussioncontrasting
confidence: 99%
“…This suggests that the role of lipids in aggressive thyroid cancer progression is mediated through APOB. Regardless of the previous findings, another study established that APOB is not associated with tumor size or the rate of lymph node metastasis in male PTC patients [180].…”
Section: Apolipoproteins In Thyroid Cancermentioning
confidence: 72%
“…A recent study found that APOA1 had an inverse relationship with tumor size in male PTC patients, especially in the younger age group after adjusting for age [180]. This study claimed that there was no association between rate of lymph node metastasis in PTC patients and serum APOA1 [180].…”
Section: Apolipoproteins In Thyroid Cancermentioning
confidence: 87%
See 1 more Smart Citation
“…At the same time, we found that the correlation between HDL‐C levels and Apo A‐I levels and the prognosis of HNSCC patients was not entirely consistent, as was the case for LDL‐C and Apo B. These phenomena also occur in other cancers: low Apo A‐I is beneficial to the prognosis of male patients with papillary thyroid cancer, but HDL‐C levels have no significant effect on the prognosis (Ma et al, 2021). In a study of middle‐aged and elderly women, the researchers found that colorectal cancer risk was positively correlated with Apo B levels and negatively correlated with HDL‐C levels, but not with LDL‐C and Apo A‐I (Chandler et al, 2016).…”
Section: Discussionmentioning
confidence: 96%